The Delta-Subunit Selective GABAA Receptor Modulator, DS2, Improves Stroke Recovery via an Anti-inflammatory Mechanism - Neumann, Silke; Boothman-Burrell, Lily; Gowing, Emma K.; Jacobsen, Thomas A.; Ahring, Philip K.; Young, Sarah L.; Sandager-Nielsen, Karin; Clarkson, Andrew N. (Frontiers in Neuroscience, 2019)
Inflammatory processes are known to contribute to tissue damage in the central nervous system (CNS) across a broad range of neurological conditions, including stroke. Gamma amino butyric acid (GABA), the main inhibitory neurotransmitter in the CNS, has been implicated in modulating peripheral immune responses by acting on GABAA receptors on antigen-presenting cells and lymphocytes. Here we investigated the effects and mechanism of action of the delta-selective compound, DS2, to improve stroke recovery and modulate inflammation. We report a decrease in NF-κB activation in innate immune cells over a wide concentration range in vitro. When DS2 was administered to LPS-challenged mice in vivo, we observed a significant decrease in the production of several pro-inflammatory cytokines. Following a photochemically-induced motor cortex stroke, treatment with DS2 at 0.1 mg/kg from 1 hour post-stroke significantly decreased circulating tumor necrosis factor (TNF)-a and interleukin (IL)-17 levels, reduced infarct size and improved motor function in mice. DS2 is thought to act as a P-glycoprotein substrate, therefore we assessed whether DS2 could cross the blood-brain-barrier (BBB). Free brain concentrations of DS2 were not affected by the presence and absence of elacridar, inhibitor of both P-glycoprotein and BCRP. Finally, as DS2 appears to dampen peripheral immune activation and only shows limited brain exposure, we assessed the role of DS2 to promote functional recovery after stroke when administered from 3-days after the stroke. Treatment with DS2 from 3-days post-stroke improved motor function on the grid-walking, but not on the cylinder task. These data highlight the need to further develop subunit-selective compounds to better understand change in GABA receptor signaling pathways both centrally and peripherally. Importantly, we show that GABA compounds such as DS2 that only shows limited brain exposure can still afford significant protection and promote functional recovery most likely via modulation of peripheral immune cells and could be given as an adjunct treatment.